2012
DOI: 10.1007/s00299-012-1312-2
|View full text |Cite
|
Sign up to set email alerts
|

GUS expression in sweet oranges (Citrus sinensis L. Osbeck) driven by three different phloem-specific promoters

Abstract: Huanglongbing (HLB) is associated with Candidatus Liberibacter spp., endogenous, sieve tube-restricted bacteria that are transmitted by citrus psyllid insect vectors. Transgenic expression in the phloem of specific genes that might affect Ca. Liberibacter spp. growth and development may be an adequate strategy to improve citrus resistance to HLB. To study specific phloem gene expression in citrus, we developed three different binary vector constructs with expression cassettes bearing the β-glucuronidase (GUS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
22

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 47 publications
1
23
0
22
Order By: Relevance
“…Miyata et al (2012) demonstrated specific GUS expression driven by the AtPP2 promoter in phloem tissue of transgenic sweet orange. However, uidA gene expression driven by this type of promoter, quantified by qPCR, is relatively lower when compared to genes driven by constitutive promoters (Dutt et al, 2012;Benyon et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Miyata et al (2012) demonstrated specific GUS expression driven by the AtPP2 promoter in phloem tissue of transgenic sweet orange. However, uidA gene expression driven by this type of promoter, quantified by qPCR, is relatively lower when compared to genes driven by constitutive promoters (Dutt et al, 2012;Benyon et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…'Pêra' and 'Valência' sweet orange cultivars were selected as the genetic material for the transformation experiments. Seed extraction, explant preparation, transformation, and plant acclimation procedures were carried out according to Miyata et al (2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Desse modo, muitos estudos estão sendo realizados, com resultados promissores, utilizando promotores de expressão preferencial no floema, como AtSuc2 (transportador de sacarose), AtPP2 (proteína de floema 2) clonados de Arabidopsis thaliana, CsPP2 (proteína de floema 2) clonado de Citrus sinensis (MIYATA et al, 2012;TAVANO, 2013) (DUTT et al, 2012;BENYON et al, 2013).…”
Section: Lista De Tabelasunclassified